Application of Google Classroom Applications as Media Thematic Learning in the Pandemic Period. Issue 1 (February 2021) - Aisyah, Nur; Rahmatullah,; Sayfullah, Hasan; Anggraini,; Kusmiati,; Sa'diya,
Abstract: This study aims to determine student understanding of the use of e-learning (Google Classroom) in supporting learning. The research method used is a qualitative method with observational and interview research procedures. The results showed that the understanding of the use of e-learning (Google Classroom) was quite easy to understand and had a positive effect in supporting learning. This shows that the students' understanding of the use of e-learning-based learning media on learning is already quite maximal, therefore it is necessary to increase the use of these learning media aspects so that e-learning based learning can run better.